Priorities for the national vaccine plan (National Academies Press, 2010)
"Vaccination is a fundamental component of preventive medicine and public health. The use of vaccines to prevent infectious diseases has resulted in dramatic decreases in disease, disability, and death in the United States and around the world. The current political, economic, and social environment presents both opportunities for and challenges to strengthening the U.S. system for developing, manufacturing, regulating, distributing, funding, and administering safe and effective vaccines for all people. Priorities for the National Vaccine Plan examines the extraordinarily complex vaccine enterprise, from research and development of new vaccines to financing and reimbursement of immunization services. The book makes recommendations about priority actions in the update to the National Vaccine Plan that are intended to achieve the objectives of disease prevention and enhancement of vaccine safety. It is centered on the plan's five goals in the areas of vaccine development, safety, communication, supply and use, and global health."--Publisher's description.